TINJAUAN HUKUM ISLAM TERHADAP STRATEGI PEMASARAN RUMAH PADA PT. PROPERTINDO JAYA BERSAMA BEKASI - Iman Supriatna; Irvan Iswandi (Jurnal Penelitian Multidisiplin Ilmu, 2022)
Housing is human basic needs and it has an extremely strategic role in forming the character and personality of a nation. It needs to be developed for the sake of life sustainability and improvement of human. However, not all people have the ability to buy a house built by the building developer caused by limited economic ability. This encourages the developer to compete building the feasible housing with reasonable price. PT. Propertindo Jaya Bersama as one of developer companies has business strategy so that middle to lower community can have their own house. In the business world, competition is a usual thing that must be faced by the entrepreneurs/businessmen, however in the competition they also must pay attention on their way business and in accordance with the Islamic Shariah. This research aims to investigate (1) how is the practice of housing marketing strategy at PT. Propertindo Jaya Bersama Bekasi, (2) how is the Islamic law review towards the housing marketing strategy at PT. Propertindo Jaya Bersama Bekasi. This research used qualitative method with case study approach. The data source collected were primary data taken from a number of respondents consisting of the house developer and the house buyer by using interview method and documentation method, while the secondary data could be through the library aiming to collect data and information with the book’s assistance obtained in the library. The research results were then analyzed using descriptive method. Based on the results of this research, PT. Propertindo Jaya Bersama applies marketing mix (4P) strategy principles namely Product, Price, Place, and Promotions. Product/goods owned by the developer have high specification. Price offered is included into cheap and sufficient category to compete with other developers. Place/location of the house being built by the developer is strategic enough and close to public facility. Promotion done by the developer is more in using electronic social media until the target of the sale aims to the millennial generation. The implementation of house business strategy applied by PT. Propertindo Jaya Bersama even though not carrying the shariah name but according to Islamic Law this business is allowed.